Influence of Organ Extracts on Blood Clotting Factors - Fantl, P; Ward, H. A (Thrombosis and Haemostasis, 1959)
Brain and lung suspensions incubated with blood or serum produce sera which are deficient in factor IX and factor VII.Suspensions prepared from acetone-dehydrated brain are effective substitutes for free phospholipids in the formation of blood thromboplastin.The fraction which inactivates the clotting factors is connected with a readily sedimentable portion of the brain suspension.It is heat stable, and destroyed by ethanol-ether extraction.The extracted lipid is inactive.